A review of cell death pathways in hemorrhagic stroke - Rinald, John H.; Troy, Carol M. (Frontiers in Cell and Developmental Biology, 2025)
Hemorrhagic stroke is a debilitating neurological disease, affecting millions worldwide. Characterized by bleeding in the brain, it is caused by a breakdown of the blood-brain barrier (BBB) and causes damage through the presence of iron in the brain, immune activation and increased intracranial pressure. The goal of this mini-review is to explore the signaling pathways that lead to cell death that are a part of disease progression in hemorrhagic stroke. This mini-review will highlight clinical observations and data, while also incorporating findings using preclinical disease models. There are important roles for apoptosis, necroptosis, necrosis, autophagy, ferroptosis, and pyroptosis in hemorrhagic stroke. Recent work has highlighted the interplay between these phenomena, providing key regulators as potential therapeutic targets, including reactive oxygen species, iron metabolism, and caspases. Therapeutic strategies that can delay or counteract the cytotoxic effects of hemorrhage can improve clinical outcomes in hemorrhagic stroke patients.